The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1088/1612-2011/13/3/035902
|View full text |Cite
|
Sign up to set email alerts
|

Photon lifetime correlated increase of Raman scattering and third-harmonic generation in silicon nanowire arrays

Abstract: Light propagation in silicon nanowire layers is studied via Raman scattering, third-harmonic generation and cross-correlation function measurements. The studied silicon nanowire arrays are characterized by a wire diameter of 50-100 nm and a layer thickness ranging from 0.2-16 μm. These structures are mesoscopic for light in the visible and near infrared ranges. The Raman signal increases monotonically with layer thickness increases at a 1.064 μm pump wavelength. The Stokes component for silicon nanowire arrays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The obtained thicknesses were 25 ± 3 μm and 80 ± 5 μm for the lowdoped and heavily-doped samples, respectively. The metal-assisted chemical etching (MACE) technique [33,36] was employed to fabricate Si-NW arrays that further served as targets for PLAL. The same two types of low-doped and heavilydoped Si wafers were etched with MACE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained thicknesses were 25 ± 3 μm and 80 ± 5 μm for the lowdoped and heavily-doped samples, respectively. The metal-assisted chemical etching (MACE) technique [33,36] was employed to fabricate Si-NW arrays that further served as targets for PLAL. The same two types of low-doped and heavilydoped Si wafers were etched with MACE.…”
Section: Methodsmentioning
confidence: 99%
“…The metal-assisted chemical etching (MACE) technique [ 33 , 36 ] was employed to fabricate Si-NW arrays that further served as targets for PLAL. The same two types of low-doped and heavily-doped Si wafers were etched with MACE.…”
Section: Methodsmentioning
confidence: 99%
“…In all, as yet it has been shown that SiNWs are found to process such remarkable optical properties as visible photoluminescence (PL) [ 91 , 92 ], very low total reflection [ 92 , 93 ], enhancement of Raman scattering [ 92 , 93 , 94 ], coherent anti-Stokes light scattering [ 95 ], interband PL [ 93 , 96 ], and efficiency of generation of third harmonics whereby light is generated at a wavelength which is one-third of the pump wavelength [ 92 , 97 ].…”
Section: Silicon Nanowire Propertiesmentioning
confidence: 99%
“…The reaction is catalyzed by metal nanoparticles such as Au [10,12], Ag [13], or Pt [10,11] at the substrate surface, and the oxidizing agents are H 2 O 2 [10][11][12][13], KMnO 4 [14], or Fe(NO 3 ) 3 [15]. It has been shown that SiNWs, which were obtained by MACE, are found to possess such remarkable optical properties as visible photoluminescence (PL) [16], extremely low total reflection [17,18], enhancement of Raman scattering [17,[19][20][21], coherent anti-Stokes light scattering [22], interband PL [17,[19][20][21] and efficiency of generation of third harmonics [23] in comparison with the corresponding intensities for c-Si, and sensitivity of visible PL to molecular surroundings [24]. However, HF is rather toxic and may also result in hypocalcemia and hypomagnesemia [25].…”
Section: Introductionmentioning
confidence: 99%